Anthrenus museorum - Majka, Christopher G. (Zenodo, 2007)
Anthrenus museorum (Linnaeus, 1761) NOVA SCOTIA: Colchester Co.: Debert, 13.v.1996, J. Ogden, JOC. PRINCE EDWARD ISLAND: Queens Co.: Brackley, 9.vii.1983, M.E.M. Smith, ACPE; Charlottetown, 16.ii.1996 and 11.iv.1997, M.E.M. Smith, (2), ACPE; Cornwall, summer 1998, M.E.M. Smith, (3), ACPE. An introduced Palearctic species, newly recorded in Nova Scotia, Prince Edward Island, and the Maritime Provinces as a whole (Fig. 4). In the USA recorded from Connecticut, Massachusetts, and Wisconsin (Beal 2003); in Canada known from Ontario, Québec, and Newfoundland (Bousquet 1991). A household pest; larvae are found on wool, fur, skins, and other animal products; also on museum specimens and insect collections. Like other species in the genus, adults feed on nectar and pollen, mate in the field, and fly indoors to oviposit (Bousquet 1990). Published as part of Majka, Christopher G., 2007, The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia), pp. 1-38 in Zootaxa 1573 (1) on page 13, DOI:10.11646/zootaxa.1573.1.1, http://zenodo.org/record/5096635